PENGARUH LAMA WAKTU FERMENTASI DAUN KELOR (Moringa oleifera) DENGAN BAKTERI ASAM LAKTAT TERHADAP KONSENTRASI ASAM AMINO - Annisa Sekar Aprisa; Dudung Angkasa; Putri Ronitawati; Reza Fadhilla; Prita Dhyani Swamilaksita (JURNAL AGROINDUSTRI HALAL, 2024)
Moringa (Moringa oleifera) is a nutrient-densed food that can be used as a food source and possess pharmacological properties. Fermented Moringa has a better amino acid profiles and potentially has a greater digestibility. Nevertheless, the effect of lactic acid bacteria as fermentation culture on Moringa’s amino acid profiles is warrant for investigation. The purpose of this study was to determine the effect of the Moringa’s fermentation with lactic acid bacteria on its nutritional value, especially amino acid. In this study, Moringa leaves were fermented with lactic acid bacteria for 0, 24, and 48 hours. Amino acid concentrations with fermentation 0, 24, and 48 hours respectively were 1007.94 mg/kg, 1304.13 mg/kg, and 521.12 mg/kg, where the highest concentration of amino acids was in Moringa leaves which were fermented for 24 hours. The concentrations of various amino acids in Moringa leaves were measured by High Performance Liquid Chromatography. The best treatment was 24 hours of fermentation, where the total amino acid (TAA) was 1304.13 mg/kg.